Uso de antídotos en un servicio de urgencias pediátricas - Martínez Sánchez, L (2014)
INTRODUCTION: Poisoning is an infrequent cause of consultation in a pediatric emergency department (PED), but it can be potentially serious. Pediatricians should know how to use the available antidotes properly. OBJECTIVES: To analyze the use of antidotes in a PED and to assess the suitability of their indications. MATERIALS AND METHODS: A retrospective review of antidote use in a PED between January 2008 and June 2012. Inclusion criteria were age younger than 18 years and consultation for suspicious poisoning by a substance that could be treated with an antidote. The adequacy of antidote indication was based on the recommendations of the Spanish Society of Pediatric Emergencies (SSPE). RESULTS: A total of 1728 consultations for suspicious poisoning (0.4% of the total visits in the PED) were recorded. In 353 cases (20.4%) the involved poison could be treated with an antidote. Sixty-seven patients received an antidote (3.9% of consultations for suspicious poisoning), and a total of 69 administrations of an antidote were made: 100% oxygen (46), N-acetylcysteine (10), flumazenil (4), naloxone (3), deferoxamine (2), vitamin K (2), bicarbonate (1), and carnitine (1). In 3 cases there was no indication for administration: flumazenil without respiratory depression, and vitamin K following coumarin exposure. As side effects, agitation was noted after the use of flumazenil, and a decrease in the prothrombin time during infusion of N-acetylcysteine. CONCLUSIONS: The administration of antidotes in this PED is uncommon and, mainly, in accordance with the SSPE recommendations, and without serious side effects. The use of flumazenil needs to be limited to the cases with a clear indication and without any contraindication.